Respostas

2014-03-09T16:30:53-03:00
OA = A - O 
OA = (-1, 3) - (0,0) 
OA = (-1, 3) 

AB = B - A 
AB = (2, 5) - (-1, 3) 
AB = (3,2) 

OA - AB= (-1,3) - (3,2) 
OA - AB= (-4, 1) 
_____________________ 
OC = C - 0 
OC = (3, -1) - (0, 0) 
OC = (3, -1) 

BC = C - B 
BC = (3, -1) - (2, 5) 
BC = (1, -6) 

OC - BC = (3, -1) - (1, -6) 
OC - BC = (2, 5) 
_____________________ 
BA = A - B 
BA = (-1,3) - (2,5) 
BA = (-3,-2) 

CB = B - C 
CB = (2,5) - (3,-1) 
CB = (-1, 6) 

3*BA - 4*CB = 
3* (-3,-2) - 4* (-1, 6) = 
(-9, -6) - (-4, 24) = 
(-5, -30)
29 4 29
Muitooooo obrigadaaaa querida! :D :D
de nada ! ;)
Muito obrigado